Collateral Damage: The Impact of Foreclosures on New Home Mortgage Lending in the 1930s. (16th September 2020) - Fishback, Price; Fleitas, Sebastian; Rose, Jonathan; Snowden, Ken
Abstract : The Great Depression of the 1930s involved a severe disruption in the supply of home mortgage credit. This paper empirically identifies a mechanism lying behind this credit crunch: the impairment of lenders' balance sheets by illiquid foreclosed real estate. With data on hundreds of building and loans (B&Ls), the leading mortgage lenders in this period, we find that the overhang of foreclosed real estate explains about 30 percent of the drop in new lending between 1930 and 1935.